Surface defect engineering: gigantic enhancement in the optical and gas detection ability of metal oxide sensor. Issue 69 (12th July 2016) - Wang, Wen-Chieh; Lai, Chun-Yen; Lin, Yu-Ting; Yua, Tzu-Hsuan; Chen, Zong-Yi; Wu, Wen-Wei; Yeh, Ping-Hung
Abstract : By using surface defect engineering, the gigantic enhancement in UV and gas detection abilities of nanosensors can be achieved. Abstract : In this work, the detection ability of nanosensors can be improved extraordinarily via surface defect engineering. A kinked SnO2− X /SnO2 nanostructure was fabricated by tuning the oxygen flow, and this kinked SnO2− X /SnO2 nanostructure was used to study the mechanism of surface defect (oxygen vacancy, VO ) effects via electric measurements. For UV light sensing, the response of the SnO2− X NW device is always better than the SnO2 NW device, and is two orders higher under pure O2 surrounding conditions. The detection mechanism can be clarified by changing the detection environment (oxygen concentration) and the UV light detection sensitivity can be improved by increasing the surface VO density. Furthermore, the SnO2− X NW device is very sensitive to its surrounding environment due to the high surface VO density. Hence, CO/O2 alternate-detection was used to verify our hypothesis; the results show that the SnO2− X NW device presents great detection abilities, compared with the SnO2 NW device. The sensitivity of the SnO2− X NW device is two orders higher and the reset/response time is faster, compared with the SnO2 NW device. To verify this hypothesis, the polycrystalline structure was fabricated to prove that the detection ability of metal oxide nanosensors can be improved gigantically by increasing surface defect amounts.